Conformance control in heterogeneous two-dimensional sandpacks by injection of oil-in-water emulsion: Theory and experiments. (1st August 2020) - Ding, Boxin; Shi, Longyang; Dong, Mingzhe
Highlights: A heterogeneous 2-D sand model was designed for flow tests of conformance control by O/W emulsion injection. Impacts of emulsion droplet size on promoting crossflow between heterogeneous zones were investigated. A new mathematical model was proposed to simulate dynamics of emulsion flow in heterogeneous porous media. The experimentally observed emulsion conformance control processes were successfully predicted. Abstract: Oil-in-water (O/W) emulsion flow tests were conducted in visual and heterogeneous two-dimensional (2-D) models in which the crossflow between the high (HPZ) and low permeability zones (LPZ) can be modelled. Impacts of emulsion droplet size on promoting crossflow between the two permeability zones were investigated. Emulsion flood pattern and outflow percentage from the two heterogeneous zones show that injection of O/W emulsions with an appropriate range of droplet sizes can induce crossflows between the two permeability zones, thereby resulting in the water mobility conformance in the heterogeneous 2-D model. Two types of crossflow were observed in the experiments and verified in the numerical modeling: flow redistribution at the injection boundary and crossflows in the emulsion-invaded area. A new mathematical model was established to capture the dynamics of 2-D emulsion flow. A finite element method was used to obtain the solution of the mathematical model, and the experimentally observed emulsion conformance control processes were successfully predicted. Mathematical analyses on emulsion concentration distribution, velocity field and pressure distribution reveal that it is the capillary resistance contributed by the emulsion that changes the pressure distribution in the two permeability zones; therefore, the changed pressure distribution affects the local flow in the two permeability zone and thus influences the outflows. The proposed emulsion flow model is compatible with a standard reservoir simulator, providing a potentially efficient and useful method of simulating field-scale emulsion flow for designing conformance control process.